Credit Counseling, Financial Coaching, and Client Outcomes: An Examination of Program Impacts and Implementation Dynamics - Roll, Stephen Patrick (ProQuest Dissertations & Theses, 2016)
Consumers in the United States are beset by a number of serious financial issues and concerns that are unlikely to disappear in the near future. When issues such as high levels of consumer debt, financial illiteracy, and suboptimal financial management skills are coupled with the vulnerability to economic fluctuations and persistently low savings levels observed in the U.S., individuals may be rendered less capable of weathering even modest income and expense shocks and may face substantial financial distress over the course of their lives. Consumer credit counseling agencies offer a means of addressing the harms and risks caused by these economic realities.Given the reach of counseling initiatives, which serve millions of people a year, there is a distinct need for rigorous assessments of credit counseling(apostrophe)s potential impact on client outcomes. Understanding the impact of these services helps validate credit counseling(apostrophe)s potential as a lever for policymakers to employ in addressing the consumer financial issues associated with both economic shocks and longer-term trends in consumer behaviors.This dissertation focuses on two interventions housed within consumer credit counseling agencies: A credit counseling program and a financial coaching program. After outlining a conceptual framework through which the potential impacts of credit counseling may be understood, this dissertation empirically explores a nationwide credit counseling initiative and outlines a profile of counseling clients. To measure the impacts of this credit counseling program relative to the counterfactual, this dissertation estimates a series of differences-in-differences models to track outcomes for over 6,000 counseling clients relative to a matched non-counseled comparison group. The key finding of this analysis is that counseling clients reduce both revolving debt and total debt relative to the comparison group and these reductions hold when controlling for debt write-offs and debt management plan participation.This dissertation then narrows its focus to examine the impact that frontline implementation dynamics have on the outcome of an experimental financial coaching program. The analysis first demonstrates that both program outputs and target group outcomes vary by the frontline worker. It explores the sources of this variation and finds that these differences are associated with differing approaches to client engagement and different levels of worker engagement with the program itself. Specifically, the analysis finds that workers who are capable of successfully engaging clients are significantly more capable of driving program enrollment, while workers who are more engaged with the program(apostrophe)s change processes are significantly more capable of driving improved client outcomes.These analyses show not only that credit counseling can drive improvements in client financial outcomes but that understanding how programs are delivered also matters in assessing outcomes. In doing so, this dissertation contributes to the broad general literature on consumer financial policies and programs and to the limited literatures on credit counseling and financial coaching, as well as both the theoretically- and empirically-oriented literatures on social service implementation in the fields of public policy and management. Further, it contributes to the emerging research on the use of behavioral economics to understand and address issues in public policy.